1975
DOI: 10.1128/jb.121.1.381-389.1975
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of colicin E2 and colicin E3 plasmid deoxyribonucleic acid EcoR-1-sensitive sites

Abstract: Colicin plasmids E2 and E3 (Col E2 and Col E3) deoxyribonucleic acid (DNA) has been shown to contain, respectively, two and three EcoR1 restriction endonuclease-sensitive sites. This was determined by measuring the DNA fragments generated after EcoR1 endonuclease treatment by agarose gel electrophoresis and electron microscopy. The structure of heteroduplex Col E2-col E3 DNA molecules formed from EcoR1-generated fragments permitted a localization of the EcoR1-sensitive sites on the plasmid chromosomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1977
1977
1985
1985

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…The molecular weights of the HaeII-generated fragments were determined by comparing them with EcoRI-generated fragments of ColEl, ColE2, and ColE3 plasmid DNAs and X phage DNA (10). ColEl is digested into six fragments ( Fig.…”
Section: Isolation Of Deletion Mutants Of Colel It Was Previously Shmentioning
confidence: 99%
“…The molecular weights of the HaeII-generated fragments were determined by comparing them with EcoRI-generated fragments of ColEl, ColE2, and ColE3 plasmid DNAs and X phage DNA (10). ColEl is digested into six fragments ( Fig.…”
Section: Isolation Of Deletion Mutants Of Colel It Was Previously Shmentioning
confidence: 99%
“…Homology is also evident in their corresponding plasmids ColE2-P9 and ColE3- CA38. Heteroduplex experiments (7,8) and a comparison of restriction maps (9,10) revealed that the major difference between these two plasmids is to be found around the limited region encoding the T2A and immunity protein of each colicin.…”
Section: Introductionmentioning
confidence: 99%
“…Locations of the colicin and immunity genes. ColE3-CA38 and ColE2-P9 are 80 to 90% homologous, and their restriction maps are very similar (5,10). Because the positions of the colicin and immunity genes of ColE3-CA38 are known (R. Watson and L. P. Visentin, submitted for publication), the positions of these genes Restriction maps and regions of nonhomology of ColE2-P9, ColE2-CA42, and ColE2-pBR322 hybrid plasmids.…”
mentioning
confidence: 99%